Immunity against diphtheria among children aged 5–17 years in India, 2017–18: a cross-sectional, population-based serosurvey. Issue 6 (June 2021) - Murhekar, Manoj V; Kamaraj, Pattabi; Kumar, Muthusamy Santhosh; Khan, Siraj Ahmed; Allam, Ramesh Reddy; Barde, Pradip V; Dwibedi, Bhagirathi; Kanungo, Suman; Mohan, Uday; Mohanty, Suman Sundar; Roy, Subarna; Sagar, Vivek; et al.
Summary: Background: Diphtheria is re-emerging as a public health problem in several Indian states. Most diphtheria cases are among children older than 5 years. In this study, we aimed to estimate age-specific immunity against diphtheria in children aged 5–17 years in India. Methods: We used residual serum samples from a cross-sectional, population-based serosurvey for dengue infection done between June 19, 2017, and April 12, 2018, to estimate the age-group-specific seroprevalence of antibodies to diphtheria in children aged 5–17 years in India. 8309 serum samples collected from 240 clusters (122 urban and 118 rural) in 60 selected districts of 15 Indian states spread across all five geographical regions (north, northeast, east, west, and south) of India were tested for the presence of IgG antibodies against diphtheria toxoid using an ELISA. We considered children with antibody concentrations of 0·1 IU/mL or greater as immune, those with levels less than 0·01 IU/mL as non-immune (and hence susceptible to diphtheria), and those with levels in the range of 0·01 to less than 0·1 IU/mL as partially immune. We calculated the weighted proportion of children who were immune, partially immune, and non-immune, with 95% CIs, for each geographical region by age group, sex, and area of residence (urban vs rural). Findings: 29·7% (95% CI 26·3–33·4) of 8309 children aged 5–17 years were immune to diphtheria, 10·5% (8·6–12·8) were non-immune, and 59·8% (56·3–63·1) were partially immune. The proportion of children aged 5–17 years who were non-immune to diphtheria ranged from 6·0% (4·2–8·3) in the south to 16·8% (11·2–24·4) in the northeast. Overall, 9·9% (7·7–12·5) of children residing in rural areas and 13·1% (10·2–16·6) residing in urban areas were non-immune to diphtheria. A higher proportion of girls than boys were non-immune to diphtheria in the northern (17·7% [12·6–24·2] vs 7·1% [4·1–11·9]; p=0·0007) and northeastern regions (20·0% [12·9–29·8] vs 12·9% [8·6–19·0]; p=0·0035). Interpretation: The findings of our serosurvey indicate that a substantial proportion of children aged 5–17 years were non-immune or partially immune to diphtheria. Transmission of diphtheria is likely to continue in India until the immunity gap is bridged through adequate coverage of primary and booster doses of diphtheria vaccine. Funding: Indian Council of Medical Research.